2015
DOI: 10.1145/2766909
|View full text |Cite
|
Sign up to set email alerts
|

Optimal presentation of imagery with focus cues on multi-plane displays

Abstract: Reproducing a real-world scene on a multi-plane display. Given a focus stack consisting of images of a scene focused at different distances, we use optimization to determine images to show on the presentation planes of the multi-plane display so that the image seen through the display when focusing at different distances matches the corresponding image of the input scene. The presentation planes combine additively in the viewer's eye to produce an image with realistic focus cues. AbstractWe present a technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 67 publications
(59 reference statements)
1
106
1
Order By: Relevance
“…Early on, Akeley et al [11] demonstrate the benefits of fixed-viewpoint volumetric desktop displays using multiple display planes and generate near-correct focus cues without tracking eye position. Recently such displays were revisited with improved scene decomposition, and gaze-contingent varifocal multi plane capabilities [12], [13]. However, these displays have large power and computational demands with a complex hardware that doesn't lead to a wearable form factor.…”
Section: Related Workmentioning
confidence: 99%
“…Early on, Akeley et al [11] demonstrate the benefits of fixed-viewpoint volumetric desktop displays using multiple display planes and generate near-correct focus cues without tracking eye position. Recently such displays were revisited with improved scene decomposition, and gaze-contingent varifocal multi plane capabilities [12], [13]. However, these displays have large power and computational demands with a complex hardware that doesn't lead to a wearable form factor.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the compressive light filed algorithm is adopted to proposed systems. Both of the proposed systems use the additive type compressive light field algorithm to interpolate the information of the two layers formed in space, and it has already been studied that accommodation of the mid-range between two layers is induced [11][12][13]. Therefore, both systems float two images with 0.3 diopter distance difference and it is generally known that mid-range depth can be expressed when two multilayer displays have a distance of about 0.3 diopter.…”
Section: Additive Type Compressive Light Field Algorithmmentioning
confidence: 99%
“…A common approach to present depth cues is by displaying virtual content on multiple transparent planes [18][19][20]. Although MacKenzie et al [21] showed that five focal planes are enough to produce an acceptable range of real-time accommodative cues, multiple focal planes lead to a bulkier HMD design.…”
Section: Displays For Refocusable Ar Contentmentioning
confidence: 99%